2021
DOI: 10.3389/fphar.2021.688508
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of an Alternative Glycyrrhizin Metabolite Causing Liquorice-Induced Pseudohyperaldosteronism and the Development of ELISA System to Detect the Predictive Biomarker

Abstract: Liquorice is usually used as crude drug in traditional Japanese Kampo medicine and traditional Chinese medicine. Liquorice-containing glycyrrhizin (GL) can cause pseudohyperaldosteronism as a side effect. Previously, we identified 18β-glycyrrhetyl-3-O-sulfate (3) as a GL metabolite in Eisai hyperbilirubinuria rats (EHBRs) with the dysfunction of multidrug resistance-related protein (Mrp2). We speculated that 3 was associated with the onset of liquorice-induced pseudohyperaldosteronism, because it was mainly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…and 18β-glycyrrhetyl-3-O-sulfate-30-glucuronide (compound 4) as other GL metabolites in the urine of EHBR orally treated with GA (34)(35)(36). We also found that the blood and urinary concentrations of these new metabolites were much higher than those of 3MGA in EHBR orally treated with GA, and that their pharmacokinetic behavior was similar to that of 3MGA (34,35).…”
Section: Gl-metabolites That Truly Reach and Inhibit Type 2 11β-hydroxysteroid Dehydrogenasesupporting
confidence: 50%
See 3 more Smart Citations
“…and 18β-glycyrrhetyl-3-O-sulfate-30-glucuronide (compound 4) as other GL metabolites in the urine of EHBR orally treated with GA (34)(35)(36). We also found that the blood and urinary concentrations of these new metabolites were much higher than those of 3MGA in EHBR orally treated with GA, and that their pharmacokinetic behavior was similar to that of 3MGA (34,35).…”
Section: Gl-metabolites That Truly Reach and Inhibit Type 2 11β-hydroxysteroid Dehydrogenasesupporting
confidence: 50%
“…As it is difficult to diagnose PsA based only on physical examination, including peripheral edema and hypertension, laboratory testing of parameters such as potassium and aldosterone levels is needed. The grade or occurrence of peripheral edema and hypertension in patients who consumed licorice did not correlate well with laboratory abnormalities, such as hypokalemia, low renin activity, aldosterone concentration, and GL metabolites (33,36). Several studies have shown the expression of mineralocorticoid receptor and 11βHSD1/2 in the heart and arteries (37)(38)(39).…”
Section: Diagnosis Of Licorice-induced Psamentioning
confidence: 92%
See 2 more Smart Citations